IMPLEMENTASI MANAJEMEN LAYANAN MARKETING DI SMA NEGERI 02 BANDAR LAMPUNG TAHUN PELAJARAN 2022/2023 - Riatrisna, Deny; Supatmi, Supatmi; Yasin, Muhammad (UNISAN JURNAL, 2023)
The current era of global competition has created a world paradigm that does not recognize the territorial boundaries of the sovereignty of a country or nation. The impact also creates higher competition in all aspects of people’s lives. Likewise with education, education management is very important, where educational institutions must create qualified management to win the competition without leaving the essence of education itself. Based on the background of this problem, the researcher wants to know the Implementation of the Marketing Management Program at SMA Negeri 02 Bandar Lampung. The method used in this study is this research is qualitative, using observation, interviews, and documentation. The data analysis technique used is an interactive model and data triangulation to check the validity of the data. The results of this study found that the Implementation of Marketing Service Management at SMA Negeri 02 Bandar Lampung was well implemented. Marketing Service Management Implementation Program at SMA Negeri 02 Bandar Lampung includes internal marketing management, external marketing management and online marketing. Two factors influence marketing management, namely supporting factors and inhibiting factors. Supporting factors include the high commitment of the school principal, the support of the school community and the commitment of the leadership. While the inhibiting factors are the lack of communication between school members due to differences in understanding, and the lack of response from the community towards the school’s approach.